Applications of Different Bioactive Glass and Glass-Ceramic Materials for Osteoconductivity and Osteoinductivity. Issue 3 (3rd July 2017) - Mahato, Arnab; Kundu, Biswanath; Mukherjee, Prasenjit; Nandi, Samit Kumar
ABSTRACT: Throughout the world, research has been carried out in development of new methods and materials involving multidisciplinary approach for effective bone tissue repair and regeneration. Amid various biomaterials, bioactive glass material has drawn considerable attention due to their superior biocompatibility, degradability, ion leaching phenomena and propagation of osteogenic cells. In this concise review, effort has been made to summarize different material combinations available as composition to elaborate their biological properties both in vitro and in vivo, reaction kinetics in simulated body fluid, effect of different constituents of bioactive glass and glassceramic compositions, porosity, etc and finally these materials' applications as bone graft substitutes and various clinical applications have been detailed. In this review an attempt has been made to sum up the recent advancement of different bioactive glass and composite materials for osteoconductivity and osteoinductivity in orthopaedic surgical challenges. GRAPHICAL ABSTRACT: